THE EFFECT OF THE CORRUPTION PERCEPTION INDEX AND PUBLIC SUPERVISION ON THE ACHIEVEMENT OF ECONOMIC GROWTH - Afrianti, Devi; Chairil Furqan , Andi; Ainil Mufidah Tanra , Andi; Ma’mun Anshori, Putra (UIN Sunan Gunung Djati Bandung, 2026)
The achievement of the Sustainable Development Goals (SDGs), particularly SDG 8 on inclusive and sustainable economic growth, faces significant challenges across many countries. One of the main obstacles is corruption, which undermines economic efficiency, reduces investment, and weakens public trust. In addition, weak public oversight leads to a lack of accountability in the management of national budgets. These issues create a need to understand the extent to which the Corruption Perceptions Index (CPI) and public oversight influence the attainment of economic growth. This study aims to empirically analyze the impact of the Corruption Perceptions Index (CPI) and public oversight on the achievement of SDG 8. The study employs secondary data sourced from Transparency International, the Worldwide Governance Indicators, and the UNDP, covering 148 countries in 2021, and uses multiple linear regression with the Human Development Index (HDI) as a control variable. The results indicate that both CPI and public oversight have a positive and significant effect on the attainment of SDG 8, while HDI shows no significant influence. These findings underscore the importance of governance integrity and effective public oversight in supporting inclusive and sustainable economic growth. They also provide implications for governments and stakeholders in formulating more responsive development policies to accelerate the achievement of SDG 8.